PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT DAN DAMPAKNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi pada Karyawan PT. Jakarta Cakratunggal Steel Mills) - Sari, Tiurma Yustisi; Pattipawae, Daniel A. W.; Kurniasih, Augustina (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The aims of this research is to analyze the effect of Transformational Leadership and Organizational Culture on Employee Engagement and its impact on Organization Citizenship Behavior. The analysis methods used in this research was path analysis. The result shows that there are positive and significant correlations among the variables of Transformational Leadership, Organizational Culture and Employee Engagement on OCB. The transformational leadership and organizational culture both influence the employee engagement with the score 0.520. Meanwhile, Transformational Leadership, Organizational Culture and Employee Engagement influence the Organizational Citizenship b\Behavior with the score 0.641, and The Organizational Culture has the most direct impact on Employee Engagement (β = 0,510). Moreover, employee engagement has the direct impact on OCB ( β = 0,348)